Triple-site radiotracer application in breast lymphoscintigraphy and sentinel node discordance - John A. Freebody (World Journal of Nuclear Medicine, 2019)
Sentinel lymph node (SLN) biopsy (SLNB) has demonstrated accuracy in the axillary staging of breast cancer patients. Despite variability in selection criteria and technique, an SLN is consistently identified in approximately 96% of cases and in most series predicts the status of remaining axillary LNs in >95% of cases. The false-negative rate of sentinel lymph node biopsy (SLNB) was originally reported as 5%–10% (sensitivity 90%–95%), but improved rates are attainable by experienced surgeons. Radiolocalization with lymphoscintigraphy (LSG) increases SLN identification rates. LSG is a useful tool to establish the abnormal lymphatic drainage patterns and to detect the extra-axillary nodes, particularly internal mammary nodes. Despite controversy regarding the optimal injection method, studies have generally suggested high concordance between the various radiotracer application sites and axillary SLN identification. Discordant SLN identification would have implications for nodal staging as the true SLN might not be identified with individual injection techniques. In the current study, imaging from consecutive patients presenting for breast LSG over a-19 month period was retrospectively reviewed. Radiotracer application was performed with simultaneous injection of peritumoral, subcutaneous, and subareolar regions. This application method provided a mechanism to assess the LSG drainage patterns with a view to assessing injection site concordance and SLN identification rates. Data from 123 breast LSG patients were reviewed. Using our radiotracer technique, the axillary SLN identification rate was 98%. A single axillary node was detected in 110, two axillary nodes were detected in 10, and no axillary node was detected in three patients. Among those 10 patients in whom two axillary nodes were seen, at least two cases of discordant drainage occurred from different injection sites. This study demonstrates that different LSG injection sites can result in the identification of different axillary sentinel nodes although this appears to be a rare event. This finding may be of clinical importance if the true SLN is sought. In addition, the multisite injection technique appears to be an optimal method of axillary SLN identification, with high SLN detection rates.